2017
DOI: 10.1292/jvms.17-0250
|View full text |Cite
|
Sign up to set email alerts
|

Reference intervals and allometric scaling of two-dimensional echocardiographic measurements in 150 healthy cats

Abstract: The objective of the study was to evaluate the effects of body weight (BW), breed, and sex on two-dimensional (2D) echocardiographic measures, reference ranges, and prediction intervals using allometrically-scaled data of left atrial (LA) and left ventricular (LV) size and LV wall thickness in healthy cats. Study type was retrospective, observational, and clinical cohort. 150 healthy cats were enrolled and 2D echocardiograms analyzed. LA diameter, LV wall thickness, and LV dimension were quantified using three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 34 publications
2
18
1
Order By: Relevance
“…adaptive concentric hypertrophy, probably because the heart needs to enhance its contraction force to maintain blood flow in a large body mass. Different from the results reported here, a previous study using allometry observed that echocardiographic measurements were influenced by body weight, mainly VSd (Karsten et al, 2017); the discrepancy between results can be due to the different methods used. Another study observed the influence of body weight on cardiac measurements, mainly in the left atrium/aorta ratio, but they did not use BSC (Häggström et al, 2016).…”
Section: Discussioncontrasting
confidence: 99%
“…adaptive concentric hypertrophy, probably because the heart needs to enhance its contraction force to maintain blood flow in a large body mass. Different from the results reported here, a previous study using allometry observed that echocardiographic measurements were influenced by body weight, mainly VSd (Karsten et al, 2017); the discrepancy between results can be due to the different methods used. Another study observed the influence of body weight on cardiac measurements, mainly in the left atrium/aorta ratio, but they did not use BSC (Häggström et al, 2016).…”
Section: Discussioncontrasting
confidence: 99%
“…This study revealed that LAD strongly correlates with BW in healthy dogs. A similar result was found in humans, cats, and horses where normalization of LAD by an allometric model successfully removes the effect of body size [7, 9, 16, 22, 28, 30, 31, 36]. Differently, the LAD did not correlate with age or sex in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, significant interoperator measurement variability of the LA/Ao has been reported, with possible misdiagnosis of LAE [27]. For these reasons, in cats and horses, the measurement of LAD is routinely used to evaluate LA size and LAE [1, 16, 31, 32, 37]. Given the correlation of LAD with body weight (BW), the normal reference range of LAD using allometric scales has been proposed in these two species [1, 16, 31, 37].…”
mentioning
confidence: 99%
“…The results of the present study in 823 clinically healthy rhesus macaques demonstrated that BW, age, HR and sex have a significant effect on various two-dimensional (2D) and M-mode echocardiographic parameters. Among all these variables, as reported in the previous studies, BW has the most significant impact on the echocardiographic measurement of left atrial and aortic diameter as well as left ventricular wall thickness during systole and diastole and performing allometric scaling eliminated the effect of BW on these measurements [18][19][20][21][22]. Therefore, using BW-based 95% prediction intervals based on allometric scaling is recommended when evaluating individual rhesus macaques.…”
Section: Discussionmentioning
confidence: 71%